A (in)visibilidade de famílias homoafetivas durante atendimentos nos serviços de saúde - Obem, Marielle Kulakowski (2018)
Family is a group of individuals linked together, whether by alliance, affiliation, adoption, kinship, cohabitation or socio-affectivity. It must be understood as a historically determined institution that corresponds to the needs of society. From this perspective, there is the recognition of the right to be family and respect for the formation of homoaffective families. Thus, the research question was formulated: how does the interactional experience of homoaffective families in the care received in health services, according to the families' perspective? And, as objective: To know the interactional experience of homoaffective families in the care received in health services, according to the families' perspective. Refers to a qualitative approach study. Nine homoaffective families participated in the study, being two male and seven female couples, living in cities in the interior of the state of Rio Grande do Sul. Semi-structured interviews were conducted with the families, the interviews occurring from March to September. 2017. The ethical aspects were respected following Resolution No. 466/2012 of the National Health Council that concerns research on human beings. Homoaffective families, when consulting in the health services, face difficulties and feel treated differently due to their family constitution. Often these families do not feel recognized within health spaces, which contributes to their non-visibility in these environments. Families also report that, although there is no spoken revelation, affective ties between the members present in the care, which are often ignored by health professionals, are perceptible. These situations, characterized as negative, cause families to fear to reveal themselves as homogenous within health spaces, because they feel they need to protect themselves as a unit and their members as individuals of prejudice and discrimination, so as not to run the risk of exposing them, if not be understood and suffer any kind of emotional discomfort during the care provided by the professionals. The (in) visibility was thus placed, in parentheses, because it is perceived that these families are often seen by health professionals, but are not recognized by them as families.